Image Segmentation Techniques Based on Fuzzy C-Means and Otsu, Applied to the Brain MRI in Tumor Detection - Riahi, Azzeddine (International Journal of Computer Sciences and Engineering, 2025)
Visual information is the richest probably different existing information sources in our daily lives. The extraction of this information by processing systems and image analysis has attracted growing interest. The image processing is a process involving several stages, that it was born from the need to replace the human observer by the machine. He works in many fields such as medicine. A must in all image analysis process is the segmentation. By providing a compact description of the image, more exploitable than all the pixels, the image segmentation facilitates automatic interpretation of an image similar to human interpretation. Indeed, she was inspired by the human visual perception system that uses the concept of similarity and difference in order to locate and delineate the objects in an image. It can be defined as following: the image segmentation is a low-level process of creating a partition of the image into subsets called regions in a way that no region is empty; the intersection between the two regions is empty and covers all regions throughout the image. A region is a set of connected pixels having common properties that differentiate the pixels neighboring regions. This task although fluently although raised by the human visual system, is actually complex and remains a challenge for the image processing community despite several decades of research. Thus, several segmentation methods have been proposed in the literature, and can be classified into three major approaches: Approach area, Approach contour, cooperative approach. This article studies the problem of segmentation of MRI brain images. We worked precisely on cooperating more automatic classifiers to exploit complementarities between different methods or operators and increase the strength of the segmentation process. Our approach focuses on the FCM algorithm (Fuzzy c-means), the sum of degrees of membership of an individual given to all possible classes being 1. To make the algorithm robust to inaccuracies and ambiguous data that can considerably affect on the classes centers, we introduce the notion of ambiguity rejection.